Correlation between Students’ Mastery of English Tenses and Students’ Achievement in Listening Autobiography Podcast - Ragdah Ainun Mardiyah; Zumirrah Alhumaira; Aurelia Hanin Salsabila (Linguistics Initiative, 2021)
This study intends to find the correlation between the students’ mastery of English tenses and students’ achievement in listening podcasts and specifically on autobiography podcasts. The researchers use a quantitative method to analyze the correlation between students’ grammar mastery and listening podcast achievement. The population of this research is the students of the English Education Department Faculty of Teaching and Educational Science of UIN Syarif Hidayatullah that consisted of 17 students. The study conducts two tests; a grammar test and a listening podcast test. Each test is given a score of 100 if the students answer all the questions correctly. The grammar test uses a gap-filling test containing 15 questions. In the listening test, the study uses an autobiography audio of Benjamin Franklin and uses a multiple-choice test containing 10 questions. The result shows that more than half of the sample got low scores in grammar but got high scores in listening comprehension. It means by using Karl Pearson’s correlation coefficient theory there is a correlation between their grammar tenses knowledge and their listening comprehension was normal positive.